Penerapan Strategi Pemasaran Digital Syariah Untuk Meningkatkan Daya Saing UMKM di Provinsi Gorontalo - Silviani Rahman; Yusran Zainuddin (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This research examines the impact of implementing sharia digital marketing strategies on the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Gorontalo Province. The massive transformation in global markets, driven by advances in digital technology, has pushed MSMEs to adopt new strategies to remain relevant and competitive. With a focus on sharia principles, such as justice, sustainability, and blessing, this research highlights the importance of incorporating ethical values ​​in digital marketing. Through in-depth analysis of previous studies, this research shows that sharia digital marketing can increase sales and success of MSME businesses. Although challenges such as lack of knowledge about digital technology and increasingly fierce competition still exist, the implementation of sharia digital marketing strategies has proven effective in expanding market reach and strengthening the position of MSMEs in an increasingly connected and competitive market. Key factors contributing to the success of this strategy include education and training, infrastructure support, and commitment to sharia values. Thus, implementing sharia digital marketing strategies is not only a necessity, but also key in supporting the growth and sustainability of MSMEs in this digital era.